1997
DOI: 10.1109/23.603803
|View full text |Cite
|
Sign up to set email alerts
|

Absolute light output of scintillators

Abstract: measurements of light output are generally accurate since they The absolute light outputs of BGO, CsI(T1) and some new Ce-doped crystals have been measured to an accuracy of about 55 % using calibrated XP2020Q photomultipliers and standard S3590-03 and S2740-03 photodiodes. The use of small crystals, 9 mm in diameter and 1 mm thick, reduces the corrections for imperfections in the light collection process and in the photoelectron collection by the photomultipliers. The measured light output of 8500k350 ph/MeV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
173
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(188 citation statements)
references
References 17 publications
13
173
1
1
Order By: Relevance
“…Moreover, LSO appears to possesses a scintillation efficienc about four times greater than BGO based on the square of the ratio of LSO to BGO energy resolution at 511 keV (Table II). This value is somewhat higher than the ratio of absolute light outputs of these two scintillators (3.2) calculated from the data of Moszynski et al [24]. However, the present experiment tends to underestimate BGO light output relative to LSO by ignoring differences between these scintillators that affect light collection efficiency e.g., differences in emission spectra, etc.…”
Section: Energy Resolutioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Moreover, LSO appears to possesses a scintillation efficienc about four times greater than BGO based on the square of the ratio of LSO to BGO energy resolution at 511 keV (Table II). This value is somewhat higher than the ratio of absolute light outputs of these two scintillators (3.2) calculated from the data of Moszynski et al [24]. However, the present experiment tends to underestimate BGO light output relative to LSO by ignoring differences between these scintillators that affect light collection efficiency e.g., differences in emission spectra, etc.…”
Section: Energy Resolutioncontrasting
confidence: 47%
“…7(b) require correction if global lower and upper energy thresholds are to be used over the entire UFOV (as was done here). This scaling, while compensating for any crystal-to-crystal variations in LSO light output [24], regional differences in optical coupling efficienc or regional PSPMT amplificatio variations, does not correct for variations in energy resolution from crystal-to-crystal and a different correction would be needed for this purpose.…”
Section: B Spatial Linearitymentioning
confidence: 99%
“…The simulations in Section III-B have been repeated with 350 electrons rms noise per photodiode, and both 20 000 and 10 000 photons per interaction. These values correspond to about the number of e-h pairs for CsI(Tl) and LSO scintillators, respectively [5]. Scintillator dimensions are 25 25 3 mm .…”
Section: E Effect Of Varying Signal-to-noise Ratio (Snr)mentioning
confidence: 93%
“…The two materials also differ in another important parameter, their light yield at RT, with the YAP:Ce value being some 50% higher (17,100 photons/MeV, vs. 11,300 for LuAP:Ce) [17]. Bartram et al [18] suggested that the deep traps responsible for the htTL glow peaks between 300 and 600 K also contribute to the loss of scintillation light at RT.…”
Section: Introductionmentioning
confidence: 99%